Guía de Flora del Parque Nacional Llanganates, en el sector de la Laguna de Anteojos - Proaño Proaño, Elisa Valeria (2018)
Llanganates National Park belongs to the National System of Protected Areas of Ecuador, despite being declared as such, the management and conservation of the species that inhabit here has not been the best and several of the PNLL resources have been affected due to the use of land by the surrounding communities; the same that have contributed to deforestation, burning of grassland, grazing, advancing agricultural frontier and pollution. One of the resources affected is “La Laguna de Anteojos”, for that reason the present investigation has been developed; obtaining as a result a guide of flora of the place that pretends to be an instrument of diffusion of the flora, because there is no corresponding record of the species that inhabit here, for which it was used direct observation, photographic record and intensive search of species sustained by a qualitative collection of botanical samples in flower; obtaining an inventory of 74 species and 28 families, of which the largest is the Asteraceae with 18 genera and 17 species, because the difference between this family and the others found is representative, it can be concluded that this is the most representative family of the place. In the conservation status of the species, revised the IUCN red list and the catalog of life of vascular plants of Ecuador; there are two vulnerable and two endangered species, which were found since 3000 to 4500m.s.m; respectively. For the elaboration of the guide, the best photographs were taken into account for its design, considering the species that were successfully identified. The guide was obtained through the website the field museum; a website dedicated to the production of field guides of all kinds of species, the same as for proper management structure in the field. The diversity of flora species in the surroundings of the Laguna de Anteojos is high, despite the deterioration caused by the activities of local human groups and visitors in specific areas, a proof of this alteration are the disturbed areas that harbor partially different flora, the conservation is an important axis for tourism, so it is suggested to implement an environmental awareness plan by the Ministry of Environment with the support of the cantonal governments that are part of the Llanganates National Park, towards the communities that are inside and outside of it, giving them another alternative development opportunity like ecotourism.